Power Relations in Black Lives : Reading African American Literature and Culture with Bourdieu and Elias (Edition 1) - Buschendorf, Christa; Buschendorf, Christa (Bielefeld transcript Verlag, 2017)
According to relational sociology, power imbalances are at the root of human conflicts and consequently shape the physical and symbolic struggles between interdependent groups or individuals. This volume highlights the role of power relations in the African American experience by applying key concepts of Pierre Bourdieu and Norbert Elias to black literature and culture. The authors offer new readings of power asymmetries as represented in works of canonical and contemporary black writers (Richard Wright, Ralph Ellison, Gwendolyn Brooks, Toni Morrison, Percival Everett, Colson Whitehead), rap music (e.g., Jay Z), images of black homelessness, and figurations of political activism (civil rights activist Bayard Rustin
English
Keywords: Literature: history & criticism; Literary Criticism; Subjects & Themes; General